Introduction of surgeon‐performed ultrasound to a head and neck clinic: indications, diagnostic adequacy and a new clinic model?. Issue 5 (30th April 2020) - Flatman, Samuel; Kwok, Matthew Ming Kei; Magarey, Matthew J. R.
Abstract: Background: Surgeon‐performed ultrasound (SUS) changes management and surgical decision‐making. It allows for immediate ultrasound‐guided fine‐needle aspiration (US‐FNA) for the work‐up of neck masses, lymph node metastases and thyroid nodules. We examined the introduction of SUS to an Australian Head and Neck cancer unit, identifying situations where it was used, and evaluated the diagnostic adequacy and accuracy of US‐FNA. Methods: A prospective database was created for all patients undergoing SUS and US‐FNA, performed by two head and neck surgeons, between September 2018 and June 2019. The data were retrospectively analysed to identify when SUS was performed. Diagnostic adequacy and accuracy of US‐FNA were determined after evaluating formal cytology and histopathology reports. Results: A total of 183 diagnostic, surveillance and interventional SUS scans were performed for multiple indications. A total of 100 US‐FNAs were performed on a number of different sites. Diagnostic adequacy and accuracy were 92% and 85%, respectively. Conclusion: After the introduction of SUS to our weekly routine head and neck cancer clinic, we identified multiple situations where it can be used successfully within our clinical landscape. Our diagnostic US‐FNA results compared favourably to current literature, without additional need for clinic attendance by consultant radiologists or pathologists, saving valuable hospital resources. This introduction proposes a promising alternative to current neck lump clinic models. Abstract : We report the introduction of surgeon‐performed ultrasound (SUS) to an Australian head and neck cancer clinic, identifying situations where it was used and the diagnostic adequacy and accuracy of US‐FNA using our technique. Favourable results within our paper support a promising alternative to current neck lump clinic models.